Testing Concurrent Object-Oriented Systems with Spec Explorer - Campbell, Colin; Grieskamp, Wolfgang; Nachmanson, Lev; Schulte, Wolfram; Tillmann, Nikolai; Veanes, Margus (Springer, 2005)
We describe a practical model-based testing tool developed at Microsoft Research called Spec Explorer. Spec Explorer enables modeling and automatic testing of concurrent object-oriented systems. These systems take inputs as well as provide outputs in form of spontaneous reactions, where inputs and outputs can be arbitrary data types, including objects. Spec Explorer is being used daily by several Microsoft product groups. The here presented techniques are used to test operating system components and Web service infrastructure.